Development and Optimization of Grape Skin Extract-Loaded Gelatin–Alginate Hydrogels: Assessment of Antioxidant and Antimicrobial Properties - Jovana Bradic; Anica Petrovic; Aleksandar Kocovic; Vukasin Ugrinovic; Suzana Popovic; Andrija Ciric; Zoran Markovic; Edina Avdovic (Pharmaceutics, 2025)
Background: In this study, we aimed to develop and optimize unique eco-friendly gelatin–alginate hydrogels enriched with sustainable grape skin extract for advanced wound healing applications. Methods: Following confirmation of the extract’s antioxidant activity, hydrogels were synthesized by varying gelatin content and CaCl2 concentration to achieve desirable crosslinking density, mechanical properties, and extract release behavior. Physicochemical characterization of hydrogels included equilibrium swelling analysis, mechanical testing, FTIR analysis, and in vitro release of extract from hydrogel. Moreover, the biocompatibility of hydrogels enriched with extract was assessed via MTT assay, while antimicrobial activity was tested against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 10145, and Candida albicans ATCC 10231. The antioxidant capacity of the hydrogels was evaluated using DPPH, ABTS, and FRAP assays. Results: Our results showed that higher gelatin and CaCl2 concentrations produced denser crosslinked networks, leading to reduced swelling and increased stiffness. Additionally, the extract exhibited a biphasic release profile from hydrogels, featuring an initial rapid release followed by sustained release over 24 h. Conclusions: The hydrogels maintained high biocompatibility and demonstrated selective antimicrobial activity, particularly against Escherichia coli, and satisfactory antioxidant activity. Obtained multifunctional sustainable hydrogels enriched with grape skin extract represent promising agents for managing skin conditions associated with oxidative stress and bacterial infections.